PERJANJIAN HUDAIBIYAH (Cermin Kepiawaian Nabi Muhammad saw. dalam Berdiplomasi) - Abu Haif, Abu (RIHLAH, 2014)
This paper explains the role of Muhammad saw as negosiatorÂ and mediator in Hudaibiyah Agreement in 628 M/6 H. The diplomation of Rasulullah in Hudaibiyah Agreement is considered as a success negotion in history. The succesfull of Rasulullah diplomation can be portreited that Rasulullah is a great and future leader. He can predict something that would happen from that agreement, he know well there should positive effect from the agreement for all muslims at the time. Although the Quraisy negotion missbivahe in front of Rasulullah and his sahabah, Rasulullah decided to ignore it. Based on cases above, it can be concluded that Rasulullah is a great, leader, and smart diplomat.